A primer of book classification - Phillips, W. Howard; Association of assistant librarians (London : Association of assistant librarians (section of the Library association), 1961)
The study of book classification seems to have turned full circle. Under the pressure of school curricular at home and abroad, a new approach to the subject is being advanced, complete with its own set of pseudo- logical principles and adorned with a highly original and exotic terminology.
Index
aia 29/6/17
Loans
Keywords: Classification; Classification- Books